(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-195-207 The relevance of this study is due to the lack of development of the problem of studying morphology based on the axiological approach and, as a result, the insufficient use of the value potential of morphology for the development of personal qualities of students, subject and meta-subject skills. The purpose of the work is to substantiate the expediency of using axiological linguistic methods in morphology lessons and, in particular, when studying the topic “Noun as a part of speech”. To achieve this goal, the following tasks were identified: firstly, to analyze the sources and substantiate the presence in the pedagogical and methodological literature of scientific prerequisites for the implementation of the axiological approach in the study of morphology; secondly, to prove the expediency of the axiological approach as a meta-approach that ensures the achievement of personal, meta-subject and subject goals in teaching the Russian (native) language; thirdly, to substantiate the axiological nature of linguistic knowledge on the topic “Noun as a part of speech” and the need to rely on it in the process of teaching the Russian (native) language. In the process of studying the problem posed, theoretical methods and analysis of empirically obtained data on the formation of students’ morphological skills were used. The article proves the pedagogical and methodological expediency of updating the axiological linguistic methodology in the study of the morphology and axiological nature of morphological knowledge on the topic "Noun as a part of speech" for the development of the student’s personality and the formation of meta-subject and subject skills. Key words: axiological linguistic methodology; morphology; noun, potential, training, education, axio-linguistic personality